Treatment of Anisometropic Amblyopia Using Bangerter Foil and Vision Therapy. - Lee, Jessi (Optometry & Visual Performance, 2017)
Background: There are many approaches to treating amblyopia; opaque patching is one of the most common. However, opaque patching is known to have limited patient compliance due to poor cosmesis and social stigma. Partial occlusion with translucent Bangerter foils is a viable alternative to opaque patching. Case Report: JR, a 12-year-old Caucasian male with refractive amblyopia, was referred for a vision therapy evaluation. In addition to reduced acuity of 20/50- OS, JR exhibited decreased accommodative and oculomotor skills. JR was fitted with a 0.3 Bangerter foil OD over his glasses to be worn 2-3 hours per day. JR was enrolled in weekly vision therapy and reevaluated after 10 and 20 sessions. After his 20-week progress check, JR's acuity improved to 20/30 OS. JR also reported a subjective improvement in reading ability and a decrease in frequency of headaches. Conclusion: Bangerter foils are an acceptable alternative to opaque patching for amblyopia treatment. When combined with active vision therapy, patients can see an increase in visual acuity, accommodative skills, and oculomotor control.